Towards development of tropical solar architecture : the use of solar chimney as stack induced ventilation strategy - Ahmad, Mohd. Hamdan; Saleh, Md. Rajeh; Hong, Lim Foo (Faculty of Built Environment, 2006)
This research investigates the possibility of using solar chimney as stack induced ventilation strategy in terraced house in Malaysia. The existing terraced house design complies with the minimum requirement of natural ventilation as stipulated in the Malaysian Uniform Building By-Law. Unfortunately, the architectural design solutions do not permit good natural ventilation for thermal comfort. This can be illustrated by the low internal air velocity and high temperature experienced during the day time. The wind effect is also not well captured especially in the single sided ventilation. Solar chimney ventilation has been suggested by many researcher as possible alternative techniques for natural ventilation. The solar chimney study in this research involved both physical modelling and computer simulation using Computational Fluid Dynamics (CFD) technique. The specific software called Flo Vent is used. Validation of CFD FloVent is done by comparing the computer simulation result with the field measurement on site and in experiment existing terraced house. The result of the final model solar chimney prototype shows that it can increase indoor air velocity until 0.8 m/s. The other important factor is that it can continuously induce the flow of natural ventilation regardless of the available wind outside of the house. This effect is significant toward improving the thermal comfort performance in the terraced house through passive natural ventilation.